Estudo experimental e teórico da dessulfurização adsortiva de diesel real usando materiais mesoporosos de alta eficiência - Sales, Rafael Viana (2020)
The burning of fossil fuels emits sulfur oxides (SOx), which negatively affect human health and the environment, in addition to being highly undesirable by oil refineries. Researchers have sought to develop alternative methods to conventional technology, hydrodesulfurization (HDS), which is an expensive and ineffective method for removing heavy sulfur molecules. Thus, in this work, the mesoporous silicas MCM-41 and SBA-15 were synthesized and modified with metallic cations Ni2+ and Ag+ for application in adsorptive desulfurization of real diesel fuel. MCM-41 was obtained from green silica (amorphous silica MPI), from beach sand, and commercial silica. The pure and modified adsorbents were characterized by X-ray diffractometry (XRD), N2 adsorption-desorption isotherms, high-resolution scanning electron microscopy by field emission (SEM-FEG), scanning transmission electron microscopy (STEM), high-resolution transmission electron microscopy (HRTEM) and X-ray excited photoelectron spectroscopy (XPS). These techniques were important for the elucidation of materials of the type MCM-41 and SBA-15. The results of the SEM-FEG and STEM micrographs coupled with X-ray spectroscopy by dispersive energy (EDX) showed a uniform dispersion of Ag nanoparticles on the supports. Molecular dynamics simulation, using the DFT/ONIOM method, and XPS data revealed that the adsorption of aromatic sulfur compounds by AgMCM-41 is controlled by the interactions between the sulfur atoms and the silver species. The best fit of the experimental data to the kinetic model of pseudo-second order and to the Langmuir equilibrium model is an indication that chemisorption mechanisms, especially -41 and AgSBA15 adsorbents, under the conditions studied, which is in agreement with the theoretical study and the XPS results. The maximum adsorptive capacities for AgMCM-41 obtained from sustainable silica and for AgSBA-15 were 31.25 mg g-1 -1, respectively. The pure and silver modified supports showed a satisfactory regeneration rate, after 5 recycling steps, using a chloroform/hexane/acetone solution.